Janus Kinase Inhibitor Baricitinib Modulates Human Innate and Adaptive Immune System - Kubo, Satoshi; Nakayamada, Shingo; Sakata, Kei; Kitanaga, Yukihiro; Ma, Xiaoxue; Lee, Seunghyun; Ishii, Akina; Yamagata, Kaoru; Nakano, Kazuhisa; Tanaka, Yoshiya (Frontiers in Immunology, 2018)
The purpose of this study was to elucidate the mechanism of action of baricitinib on JAK/STAT signaling, which involves in human innate and adaptive immune system. The effects of baricitinib were evaluated using human monocyte-derived dendritic cells (MoDCs), plasmacytoid dendritic cells (pDCs), B cells and T cells. Baricitinib concentration-dependently suppressed the expression of CD80/CD86 on MoDCs and the production of type-I IFN by pDCs. Baricitinib also suppressed the differentiation of human B cells into plasmablasts by B cell receptor and type-I IFN stimuli, and inhibited the production of IL-6 from B cells. Human CD4+ T cells proliferated after T cell receptor stimulation with anti-CD3 and anti-CD28 antibody; however, such proliferation was suppressed by baricitinib in a concentration-dependent manner. In addition, baricitinib inhibited Th1 differentiation after IL-12 stimulation and Th17 differentiation by TGF-β1, IL-6, IL-1β and IL-23 stimulation. Tofacitinib showed similar effects in these experiments. In naive CD4+ T cells, IFN-α and IFN-γ induced phosphorylation of STAT1, which was inhibited by baricitinib as well as tofacitinib. Furthermore, IL-6-induced phosphorylation of STAT1 and STAT3 was also inhibited by JAK inhibitors. In conclusion, the results indicated that baricitinib suppresses the differentiation of plasmablasts, Th1 and Th17 cells, as well as innate immunity, such as the T cell stimulatory capacity of DCs. Thus, JAK inhibitors can be potentially clinically effective not only in rheumatoid arthritis but other immune-related diseases.